Farmers' willingness to pay for Sinar donkey conservation in selected districts of Metekel and Assosa zones, northwest Ethiopia: a contingent valuation study - Awoke Melak; TEKLEWELD BELAYHUN; ESHO KEFYALEW; ABEBE HAILU; AMINE MUSTEFA; ABRAHAM ASSEFA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Melak A, Belayhun T, Kefyalew E, Hailu A, Mustefa A, Assefa A. 2020. Farmers' willingness to pay for Sinar donkey conservation in selected districts of Metekel and Assosa zones, northwest Ethiopia: a contingent valuation study. Biodiversitas 21: 3373-3379. A survey was conducted through single field visits and interviews with 160 respondents in selected districts of Assosa and Metekel Zones, Northwestern Ethiopia, to elicit farmers' willingness to pay for Sinar donkey conservation. Two districts namely Guba and Sherkole were purposively selected from the zones based on the availability of Sinar donkey breeds. Eight representative kebeles were selected from the two districts. A total of 160 households (each district 80 households) were selected randomly. Structured and semi-structured questionnaires were prepared to collect data on socio-economic and farming system characteristics. Descriptive statistics were employed to summarize data and average means were compared using SPSS version 23.0 software. Logistic regression was applied to see the effect of independent variables on the dependent variable. The contingent valuation method was used to know farmers' willingness to pay for conservation of the Sinar donkey breed. The average willingness to pay for the conservation was 98.25 Ethiopian Birr or 3.265US dollars for the conservation program per household per annum. The cash income of the respondents influenced the willingness to pay for the conservation program. This study supports the view that the economic valuation of donkey genetic resources can assist policymakers in setting conservation priorities.